Numerical simulation of the fire resistance of composite slabs with steel deck - A. G. Piloto, Paulo; M.S. Prates, Lucas; Balsa, Carlos; Rigobello, Ronaldo (International Journal of Engineering and Technology, 2018)
This investigation is related with the fire resistance of composite slabs with steel deck. This composite solution consists of a concrete topping cast on the top of a steel deck. The concrete is typically reinforced with a steel mesh and may also contain individual rebars. The deck also acts as reinforcement and may be exposed to accidental fire conditions from the bottom. This composite solution is widely used in every type of buildings and requires fire resistance, in accordance to regulations. The fire resistance is specified by the loadbearing capacity (R), insulation (I) and integrity (E). The fire rating for (R) and (E) is not in the scope of this investigation. The fire rating for insulation (I) is evaluated by two different methods (numerical simulation and simple calculation). The fire rating is calculated for 32 different geometric configuration, in order to evaluate the effect of the thickness of the concrete layer and the thickness of steel deck. The fire resistance (I) increases with the thickness of the concrete when using both methods, but the simple calculation method seems to be unsafe for all the cases, requiring a revision for the formulae presented in Annex D of EN1994-1-2. A new proposal is presented.Â Â